Do ESG Strategies Foster or Impede Corporate Innovation: Evidence from Asia-Pacific - Al-Jaifi, Hamdan Amer Ali (Conference Series, 2021)
This study examines the joint and separate effects of Environmental (E), Social (S), and Governance (G) scores on corporate innovation. Using a 5,566 yearly-firms observation from listed firms operating in the Asia Pacific region over 2011–2020, the study finds that the aggregate ESG score and its two sub-pillars (social and governance) have insignificant impacts on corporate innovations. However, environmental activities have a significant and negative impact on corporate innovation. This finding implies that environmental activities stipulate corporate innovation as it deviates firms’ resources from the value-added activities that enhance innovation. Hence, firms need to consider the trade-off between engaging highly in environmental activities and impeding corporate innovation. These findings enrich the literature of ESG and innovation and provide valuable information for firms and their stakeholders, including regulators.